'Money has More Weight than the Man': Masculinities in the Marriages of Angolan War Veterans. (January 2014) - Spall, John
Abstract This article discusses how male Angolan war veterans navigated the sudden shift from the rigours of military discipline to life in a civilian society they no longer recognised, where money had become a dominant social value. Based on a year of participant observation and interviews with war veterans in the city of Huambo, it traces their life histories and their post‐war struggles to develop the necessary creativity and initiative to make a profit in a disordered, war‐torn economy, where masculine status and authority had come to depend crucially on monetary income. I analyse their reaction to the crumbling of the relative certainties of the patriarchal orders of both pre‐war society and military life, and the associated anxieties around living up to a senior masculine archetype of the wise, authoritative provider whilst attempting to ensure that their wives' behaviour conformed to the family model that accompanies this archetype.